2018
DOI: 10.1002/er.4202
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic characteristics of the local current density in proton exchange membrane fuel cells with different operating conditions

Abstract: Summary The present study reports an experimental investigation regarding the dynamic characteristics of local current density in proton exchange membrane fuel cells during dynamic operation, important for mobile applications, by using segmented current collector method. The results indicate that for fully humidified operation, the local current density fluctuates more intensely when the cell potential is reduced, corresponding to an increase in the average cell current density (or load), whereas it is reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…One of the possible reasons is that at lower current density, the pressure at the outlet is higher (assuming the same inlet pressure, 0.3 barg, in all conditions) compared with that at higher current densities, as less hydrogen is consumed at lower current densities. It is shown that higher outlet pressures result in fluctuation in performance as water removal become less effective . Another possible reason for this can be the temperature difference between the anode and cathode inlets.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the possible reasons is that at lower current density, the pressure at the outlet is higher (assuming the same inlet pressure, 0.3 barg, in all conditions) compared with that at higher current densities, as less hydrogen is consumed at lower current densities. It is shown that higher outlet pressures result in fluctuation in performance as water removal become less effective . Another possible reason for this can be the temperature difference between the anode and cathode inlets.…”
Section: Resultsmentioning
confidence: 99%
“…It is shown that higher outlet pressures result in fluctuation in performance as water removal become less effective. 68 Another possible reason for this can be the temperature difference between the anode and cathode inlets. Anode inlet temperature is kept at room temperature (ie, 20°C), and more hydrogen purge means more local temperature change in the MEA (ie, more hydrogen flow brings the local MEA temperature down) that can promote the liquid water build-up at the anode side.…”
Section: The Effect Of Temperature On Optimum Purge Intervalmentioning
confidence: 99%
“…1,2 Proton exchange membrane fuel cells (PEMFCs) have been recognized as one of the most promising power sources for mobile and stationary application, due to its high power density, low operating temperature and zero emissions. [3][4][5] However, there are still many challenges for its widespread commercial application, such as water management. [6][7][8] Proton exchange membrane needs to be fully hydrated to maintain high conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic operating conditions, such as startup and shutdown, could cause performance degradation and dramatic loss in durability . Thus, understanding transient characteristics of the cell during startup/shutdown processes is of great importance to optimizing operation strategy and improving fuel cell durability and stability …”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] Thus, understanding transient characteristics of the cell during startup/ shutdown processes is of great importance to optimizing operation strategy and improving fuel cell durability and stability. 14 During the startup/shutdown processes, the hydrogen/air boundary could form in the flow field, 15,16 and high potential 15,17,18 is locally present on the electrode, causing reverse current in the cell and carbon corrosion, as well as Pt oxidation and dissolution in the catalyst layer. 1,19,20 Thus, the cell durability is significantly reduced, and it is necessary to devote efforts to investigating the reverse current during startup/shutdown processes.…”
Section: Introductionmentioning
confidence: 99%